Problematika Guru Pendidikan Agama Islam (PAI) Dalam Membangun Karakter Siswa Di Sekolah Dasar Pada Masa Pandemi Covid-19 - Mariyanto; Sukino, Arief; Mahrus, Erwin (Islamic Insights Journal, 2023)
This study aims to determine the role of Islamic Religious Education teachers in building student characteristics in Elementary Schools during the Covid-19 pandemic and the constraints of Islamic Religious Education teachers in building student character in Elementary Schools during the Covid-19 pandemic. This research uses a qualitative approach with literature research methods. The collection technique used is document study, and the data analysis used is content analysis. The results showed that the learning process of Islamic Religious Education is not only cognitive but also affective and psychomotor. Islamic Religious Education in building student character in elementary schools can be done in various ways, but the most important thing is that a teacher can adapt to the times and can also determine effective learning strategies, especially in the learning process carried out online, considering that during the Covid-19 pandemic, learning was carried out online. In addition, a teacher must also be able to master competencies as an educator, namely professional, pedagogic, social, and personality. The obstacle experienced by Islam Religious Education teachers in building student character in elementary schools during the Covid-19 pandemic is that they have not mastered pedagogic competence so the learning method applied is monotonous, namely assignment. There are still many teachers who have not been able to adapt to the times, especially technology so the learning media used are less varied. There are still teachers who take actions that are not in accordance with Islamic religious teachings, Such as gambling, cheating, and justifying all means to get a certain position, especially to become a school principal.